Effect Of Motivation Learning , Classroom Climate And Student Perception About Teacher Competence Achievement Of Accounting Student Learning Class XI SMK N 1 Painan - Yuliharnis, Intan - (Pendidikan Ekonomi, 2014)
This study aims to analyze : 1 ) The effect of achievement motivation toward learning accounting class XI student of SMK N 1 Painan . 2 ) The effect of climate on learning achievement accounting class XI student of SMK N 1 Painan . 3 ) The effect of students perceptions of teacher competence on accounting students learning achievement of class XI SMK N 1 Painan . 4 ) The effect of Motivation Learning , Classroom Climate and Student Perceptions About Teacher Competency Achievement Against Accounting Students of class XI SMK N 1 Painan . This research is a descriptive study associative . The study population was all students in class XI SMK N 1 Painan numbered 300 people . Sampling technique with proportional random sampling with a sample size of 172 people . Data analysis techniques : descriptive analysis and inductive. Hasil analysis showed that: First, motivation to learn and a significant positive effect on learning achievement accounting class XI student of SMK N 1 Painan , which is indicated by the value of the coefficient of 0.270 . Value of this coefficient is significant because tcount 3,015 > 1,653 ttable with significant value 0.003 < Î± = 0.05 , then reject H0 and accept Ha . This means that if the motivation to learn to ride one percent , then the learning achievement Accounting will increase by 0,270 units . Secondly, Climate class significant and positive impact on the learning achievement of students of class XI accounting SMK N 1 Painan , which is indicated by the value of the coefficient of 0.260 . Value of this coefficient is significant because tcount 2.627 > 1.653 and significant ttable 0.009 < Î± = 0.05 , then reject H0 and accept Ha . This means that if the classroom climate rose one percent , then the learning achievement Accounting will increase by 0,260 units . Third, students perception of teacher competency significant and positive impact on learning achievement accounting class XI student of SMK N 1 Painan , which is indicated by the value of the coefficient of 0.143 . Value of this coefficient is significant because tcount , 3,994 > 1,653 ttable with significant value of 0.000 < Î± = 0.05 , then reject H0 and accept Ha . This means that if the classroom climate rose one percent , then the learning achievement Accounting will increase by 0.143 units . Fourth, learning motivation , classroom climate and students perceptions of teacher competence simultaneously positive and significant impact on learning achievement accounting class XI student of SMK N 1 Painan , which is indicated by the value of F 96.531 > F 3.05 and significant value 0.000 < Î± = 0 , 05 , then reject H0 and accept Ha . That is the motivation of learning , classroom climate and students perceptions of teacher competence is able to influence the variance in learning achievement was 63.3 % and the rest is explained by other variables